2020
DOI: 10.1200/edbk_281139
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Practice: Implementation of Strategies to Reduce Acute Care Visits in Patients With Cancer

Abstract: Patients with cancer frequently seek acute care as a result of complications of their disease and adverse effects of treatment. This acute care comes at high cost to the health care system and often results in suboptimal outcomes for patients and their caregivers. The Department of Health and Human Services has identified this as a gap in our care of patients with cancer and has called for quality-improvement efforts to reduce this acute care. We highlight the efforts of three centers—a community practice, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…38 By utilizing the symptom complexity algorithm, the escalation of common symptoms could be identified earlier and managed in the ambulatory setting, potentially eliminating the need for many acute care visits. 39 Although this study focused on symptom complexity, we also found significant associations between several sociodemographic characteristics and acute care utilization. Patients living in rural areas were more likely to visit EDs and have HAs.…”
Section: Discussionmentioning
confidence: 65%
“…38 By utilizing the symptom complexity algorithm, the escalation of common symptoms could be identified earlier and managed in the ambulatory setting, potentially eliminating the need for many acute care visits. 39 Although this study focused on symptom complexity, we also found significant associations between several sociodemographic characteristics and acute care utilization. Patients living in rural areas were more likely to visit EDs and have HAs.…”
Section: Discussionmentioning
confidence: 65%
“…The daily cadence allowed for the capture of this data, which could be used in future prognostic analytics to triage patients in need of enhanced supportive care and to help prevent these acute events, which come at high cost to the patient and health care system. 21 For example, we found that patients with 4 red alerts on their daily assessment had a 12.6% chance of an acute care visit within the next 7 days and were 4.3-fold more likely to have such an event than patients completing the assessment without a red alert. Unfortunately, despite the clinical team knowing of these red alert symptoms, patients sometimes ended up in the emergency department, indicating that perhaps some conditions cannot be managed remotely or that there is potentially a need for improved virtual supportive care delivery to manage these symptoms.…”
Section: Discussionmentioning
confidence: 83%
“… Patients exited the program when they were no longer on active treatment. Program details are presented elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…16,17 Now we face an intensification of activity due to the epidemiologic tendencies described, among these a greater number of patients who remain in treatment for longer time, more frequent unplanned accesses, and so on. 18 Accordingly, it will be increasingly important to pursue appropriateness as rigorously as possible and to adequately consider the value of what we do.…”
Section: Growing Prevalencementioning
confidence: 99%